Cavern of the Fear - Rodda, Emily (New York : Scholastic Inc., 2002)
King Lief and his friends Barda and Jasmine go in search of a weapon powerful enough to combat the Shadow Lord's magic that is keeping thousands of their fellow Deltorans prisoner in the terrifying kingdom of Shadowlands.
G4
Keywords: Magic -- Juvenile fiction; Quests (Expeditions) -- Juvenile fiction; Magic -- Fiction; Kings, queens, rulers, etc. -- Fiction; Fantasy